Controlling mixed conductivity in Na1/2Bi1/2TiO3 using A-site non-stoichiometry and Nb-donor doping. Issue 24 (31st May 2016) - Li, Linhao; Li, Ming; Zhang, Huairuo; Reaney, Ian M.; Sinclair, Derek C.
Abstract : Bi-excess and Nb-doping can both be used to fine-tune the Na0.5 Bi0.5 TiO3 oxygen-ion transport number from near zero to one. Abstract : Precise control of electronic and/or ionic conductivity in electroceramics is crucial to achieve the desired functional properties as well as to improve manufacturing practices. We recently reported the conventional piezoelectric material Na1/2 Bi1/2 TiO3 (NBT) can be tuned into a novel oxide-ion conductor with an oxide-ion transport number ( t ion ) > 0.9 by creating bismuth and oxygen vacancies. A small Bi-excess in the nominal starting composition (Na0.50 Bi0.50+ x TiO3+3 x /2, x = 0.01) or Nb-donor doping (Na0.50 Bi0.50 Ti1− y Nb y O3+ y /2, 0.005 ≤ y ≤ 0.030) can reduce significantly the electrical conductivity to create dielectric behaviour by filling oxygen vacancies and suppressing oxide ion conduction ( t ion ≤ 0.10). Here we show a further increase in the starting Bi-excess content (0.02 ≤ x ≤ 0.10) reintroduces significant levels of oxide-ion conductivity and increases t ion ∼ 0.4–0.6 to create mixed ionic/electronic behaviour. The switch from insulating to mixed conducting behaviour for x > 0.01 is linked to the presence of Bi-rich secondary phases and we discuss possible explanations for this effect. Mixed conducting behaviour with t ion ∼ 0.5–0.6 can also be achieved with lower levels of Nb-doping ( y ∼ 0.003) due to incomplete filling of oxygen vacancies without the presence of secondary phases. NBT can now be compositionally tailored to exhibit three types of electrical behaviour; Type I (oxide-ion conductor); Type II (mixed ionic-electronic conductor); Type III (insulator) and these results reveal an approach to fine-tune t ion in NBT from near unity to zero. In addition to developing new oxide-ion and now mixed ionic/electronic NBT-based conductors, this flexibility in control of oxygen vacancies allows fine-tuning of both the dielectric/piezoelectric properties and design manufacturing practices for NBT-based multilayer piezoelectric devices.